Novel Gradient p-Doping Strategy Enables Efficient Carbon-Based Hole Transport Layer-Free Perovskite Solar Cells - Xiang, Junwei; Jiang, Siqi; Cheng, Yanjie; Du, Weiting; Shi, Yuan; Shen, Song; Zhang, Bolun; Yue, Qian; Xu, Xinyi; Mei, Anyi; Zhou, Yang; Zhou, Yinhua; et al. (Nano-Micro Letters, 2026)
Carbon-based hole transport layer-free (HTL-free) printable mesoscopic perovskite solar cells (p-MPSCs) are highly attractive for their low-cost and scalable fabrication. However, the intrinsically n-type nature of the perovskite, combined with the lack of an HTL, severely impedes hole extraction and limits device performance. In this work, we innovatively introduce a polymer with strong electron-withdrawing capability as an additive into p-MPSCs. Owing to its large molecular size, this polymer spontaneously forms a negative gradient distribution from top to bottom within the mesoporous scaffold during fabrication. This distribution creates a favorable gradient p-doping profile within p-MPSCs, which facilitates more efficient hole transport, a finding corroborated by combined device simulation and cross-sectional photoluminescence mapping. Consequently, the optimized p-MPSCs exhibit an average open-circuit voltage enhancement of over 50 mV, a steady-state power conversion efficiency of 21.56% and operational stability exceeding 1500 h at 55 °C under simulated 1-sun illumination using a halogen lamp without a UV filter. Highlights: 1 A novel strategy of creating spontaneous formation of gradient p-doping in perovskite embedded in mesoporous oxide scaffold is developed. 2 The feasibility of implementing a gradient p-doping strategy in printable mesoscopic perovskite solar cells is demonstrated for the first time through combined device simulations and cross-sectional photoluminescence mapping. 3 The resulting carbon-based hole transport layer-free solar cell exhibits outstanding power conversion efficiency along with superior operational stability over 1500 h without UV filter at 55 °C.